Pengaruh Kompensasi dan Pengembangan Karir Terhadap Kinerja Karyawan pada PT. Aburahmi Di Penukal Abab Lematang Ilir (PALI) - Putri Wulandari; Roswaty Roswaty; Muhammad Bahrul Ulum (Universitas Batanghari Jambi, 2023)
The purpose of this study was to determine the Effect of Compensation and Career Development on Employee Performance at PT Aburahmi in PALI Regency. This research was conducted on PT. Aburahmi employees at Penukal Abab Lematang Ilir (PALI) jerus. 55 respondents as a sample. The data source in this study were secondary data and primary data using saturated sampling technique. Based on the results of the analysis, it shows that compensation and career development have a positive and significant effect on employee performance at Penukal Abab Lematang Ilir (PALI). F test (simultaneous) shows that Compensation and Csreer Development both have an effect on Employee Performance at Penukal Abab Lematang Ilir (PALI). Viewed and the coefficient of determination R Square is 0.274 which means 27,4% of employee performance variables can be explained by compensation and career development as much 72,6% can be explained by other variables not included in this study.